Effect of rGO nanosheet loading in SiO2/rGO hybrid nanocomposites for enhancing optoelectrical, physical, and electrochemical properties - Khammahong, Sunisar; Phrompet, Chaiwat; Ruttanapun, Chesta; Sriwong, Chaval (My University, 2025)
In this study, silicon dioxide nanoparticles (SiO2NPs) mixed with reduced graphene oxide nanosheets (rGONS) and hybrid nanocomposites (S/rGOHNCs) were synthesized to study the opto-electrical, physical and electrochemical properties. S/rGOx%HNCs samples with rGONS at various loadings (10, 30, 50, and 70 wt%) were prepared SiO2NPs and rGONS suspensions in ultrasonication process by conventional heating. The SiO2NPs, rGONS and S/rGOx%HNCs were characterized and properties confirmed by XRD, Raman spectroscopy, FT-IR spectra, UV–Vis, SEM, EDX and TGA techniques. The electrical conductivity carrier concentration, energy gap, and dielectric constant increased with rGONS loading. The S/rGO30HNCs exhibited the highest thermal conductivity, 0.7 W/m·K, and Vickers microhardness, 41.0 HV. The value of electrochemical capacity of S/rGO70HNCs, 66.95 F/g, was due to the appropriate ratio of rGONS and SiO2NPs which significantly contributed to increasing redox reaction. The findings offered SiO2NPs mixed rGONS hybrid nanocomposites with enhanced optoelectrical (electrical, optical, dielectric), physical (mechanical, thermal) and electrochemical properties.
Keywords: Electrical transport property; Nanocomposites; Reduced graphene oxide nanosheets (rGONS); Silicon dioxide nanoparticles (SiO2NPs); Thermal property